Expanding Functionality of Commercial Optical Coherence Tomography Systems by Integrating a Custom Endoscope - Welge, Weston A. (PLoS One, 2015)
Optical coherence tomography (OCT) is a useful imaging modality for detecting and monitoring diseases of the gastrointestinal tract and other tubular structures. The non-destructiveness of OCT enables time-serial studies in animal models. While turnkey commercial research OCT systems are plenty, researchers often require custom imaging probes. We describe the integration of a custom endoscope with a commercial swept-source OCT system and generalize this description to any imaging probe and OCT system. A numerical dispersion compensation method is also described. Example images demonstrate that OCT can visualize the mouse colon crypt structure and detect adenoma in vivo.